(E)-5-hydroxy-7-methoxy-3-(2′-hydroxybenzyl)-4-chromanone isolated from Portulaca oleracea L. suppresses LPS-induced inflammation in RAW 264.7 macrophages by downregulating inflammatory factors. (3rd September 2021) - Kang, Eunji; Park, Jae Eun; Seo, Youngwan; Han, Ji Sook
Abstract: Context: Portulaca oleracea L. is herbaceous succulent annual plant, which belongs to the Portulacaceae family. Many studies have shown its wide spectrum of pharmacological activities such as anti-cancer and anti-diabetic effects. Objectives: The objective of this study was to identify the anti-inflammatory effects of HM-chromanone isolated from Portulaca oleracea L. in LPS-stimulated RAW 264.7 macrophages. Materials and methods: LPS (1 μg/ml)-stimulated mouse RAW 264.7 macrophages were used to assess the anti-inflammatory effect of HM-chromanone (10–50 μM). Cell viability was evaluated by MTT assay. In addition, the production of intracellular ROS, superoxide anion, lipid peroxide, NO, and PGE2, and activity of antioxidant enzymes were analyzed. The expressions of iNOS, COX-2, IκB, NF-κB, TNF-α, IL-1β and IL-6 were evaluated by western blot analysis. Results: HM-chromanone has demonstrated that there is no significant cytotoxic effect on the viability of RAW 264.7 macrophages. In LPS-stimulated RAW 264.7 cells, HM-chromanone treatment was found to significantly inhibit the production of intracellular ROS, superoxide anion and lipid peroxide, while enhancing the activity of antioxidant enzymes such as SOD, catalase, and GSH-px. Additionally, HM-chromanone treatment was observed to inhibit NO and PGE2 production by inhibiting the expression of iNOS and COX-2. Subsequently, HM-chromanone was observed to significantly suppress LPS-induced expression of IκB, NF-κB, TNF-α, IL-1β and IL-6. Discussion and conclusion: Overall, our results suggested that HM-chromanone suppresses LPS-induced inflammation in RAW 264.7 macrophages by downregulating the expression of inflammatory factors.